(untitled) (Technical Journal, 2023)
Excessive use of fossil fuel like gasoline and increasing number of automobiles has led to extensive scientific research in the field of alternative fuel sources. Also due to the vast range of uses of plastics across many industries, Plastic Waste in landfills and global production of plastic increased over time. The conversion of Waste plastic into liquid and gaseous fuels and value-added chemicals by pyrolysis followed by fractional distillation is explained as a practical and sustainable solution for recycling plastics because the calorific value of plastic is almost identical to that of hydrocarbon fuel. This research work is focused on converting high density plastic into liquid fuel by pyrolysis at temperature 200-400℃. The obtained liquid fuel was subjected to distillation at different temperature ranges. The density and viscosity of distilled sample was measured and was found to be close to that of petrol.